Yield stability of hybrid and open pollinated tomato cultivars in Latin America and Caribbean - Ortíz, R.; Izquierdo, J. (1994)
The environment substantially affects the performance of tomato (Lycopersicon esculentum Mill.) genotypes in Latin America and the Caribbean (LAC). Therefore, stability analysis can be used to select stable, high-yielding genotypes. Nine open-pollinated and six hybrid tomato genotypes and the most representative local tomato cultivar were evaluated at 20 LAC locations. Each cultivar's yield stability was quantified using the regression of individual genotype's yield on the environmental index, which was measured by the mean of all the genotypes grown in an environment. A high-yielding and stable tomato cultivar had a mean yield higher than the general mean, b1 (coefficient of regression) = 1,Sd(2) (deviation from linearity) = 0, and r2 (coefficient of determination) > 0.50. 'Narita' (hybrid) and 'Dina RPs' (open-pollinated) were the most stable genotypes for marketable-fruit yield in LAC. 'Flora Dade', an open-pollinated genotype that is grown widely in LAC had unstable marketable-fruit yield. Neither heterogenous composition of an open-pollinated genotype nor heterozygosity per se of the hybrids could explain the yield stability achievement across environments. Therefore, alleles that confer broader adaptation might be required to achieve tomato yield stability across environments. Hence, it is possible to select for yield stability in tomato.